2012
DOI: 10.1152/ajpregu.00337.2011
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated declines in mitochondrial biogenesis and protein quality control factors are minimized by exercise training

Abstract: A decline in mitochondrial biogenesis and mitochondrial protein quality control in skeletal muscle is a common finding in aging, but exercise training has been suggested as a possible cure. In this report, we tested the hypothesis that moderate-intensity exercise training could prevent the age-associated deterioration in mitochondrial biogenesis in the gastrocnemius muscle of Wistar rats. Exercise training, consisting of treadmill running at 60% of the initial V̇o2max, reversed or attenuated significant age-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 58 publications
(85 reference statements)
11
115
0
2
Order By: Relevance
“…Because p53 is deacetylated by SIRT1 the Acp53/p53 ratio was used to assess the activity of SIRT1 (Chung et al 2015;Feng et al 2015;Kim et al 2016;Li et al 2015;Song et al 2015;Weidele et al 2017) and the results showed that exercise and NAM treatment as well as the combined effects of these increased the activity of SIRT1 in old muscle. In terms of exercise training this is similar to our earlier results (Koltai et al 2010(Koltai et al , 2012 however, the intensity of training was much less than that used in those studies. Interestingly, NAM, which can inhibit SIRT1 in certain concentrations, did not alter SIRT1 activity, suggesting that in skeletal muscle of aged Results are expressed mean ± SD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Because p53 is deacetylated by SIRT1 the Acp53/p53 ratio was used to assess the activity of SIRT1 (Chung et al 2015;Feng et al 2015;Kim et al 2016;Li et al 2015;Song et al 2015;Weidele et al 2017) and the results showed that exercise and NAM treatment as well as the combined effects of these increased the activity of SIRT1 in old muscle. In terms of exercise training this is similar to our earlier results (Koltai et al 2010(Koltai et al , 2012 however, the intensity of training was much less than that used in those studies. Interestingly, NAM, which can inhibit SIRT1 in certain concentrations, did not alter SIRT1 activity, suggesting that in skeletal muscle of aged Results are expressed mean ± SD.…”
Section: Discussionsupporting
confidence: 90%
“…It is made from L-tryptophan through kynurenine. Besides being important to NAD synthesis, NAM can inhibit the activity of SIRT1, the enzyme which appears to be important in a wide range of physiological processes including mitochondrial biogenesis (Koltai et al 2012), DNA repair (Sarga et al 2013), metabolism (MoralesAlamo and Calbet 2016) and apoptosis (Joseph et al 2013;Radak et al 2013), among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conclusions were drawn with skeletal muscle, whereby exercise counterbalanced the age-associated decline in NAMPT content and decrease in SIRT1 activity [42]. Data indicate that exercise can attenuate the age-associated decrease in mitochondrial protein synthesis in skeletal muscle of rats, which included the loss of SIRT1 and PGC-1a levels as well [149]. Similar data have been reported for mouse liver [150].…”
Section: Regulation Of Sirtuins By Cr and Exercisesupporting
confidence: 74%
“…The fluorescence intensity unit was normalized with the protein content and expressed in relative unit production per minute. The protein carbonyl measurement was assessed as described earlier (Koltai et al 2012).…”
Section: Ros and Protein Carbonyl Content And Antioxidant Enzyme Actmentioning
confidence: 99%